Examining the Effectiveness of Mindfulness Based Training Program on Female Handball Players' Psychological Skills and Coping with Stress Strategies - Zeynep Ayça Terzioğlu; Mustafa Yıldız; S. Gülfem Çakır (Selcuk University, 2020)
The aim of this study is to examine the effectiveness of a mindfulness-based training program on female handball athletes' psychological skills and strategies to cope with stress in sport. In the study, as a quasi-experimental method, pre-test, and post-test models without a control group were used. The study group consists of 9 female handball players who play in the Antalya Muratpaşa Municipality Women's Handball Team. In the research, a personal information questionnaire, the Athletic Coping Skills Inventory and Coping Strategies in Sport Competition Inventory were used to collect data as pre-test before the program and as post-test at the end of the program. In the study, the Mindfulness-Based Training Program was implemented once a week as group training, consisting of 8 sessions lasted 60 minutes each. Wilcoxon Signed Rank Test was used to test the significance of the scope difference. As a result of the study, after the program, there was a significant difference in terms of ability to cope with adversity, coachability, concentration, goal setting and mental preparation, and being free from worries. Moreover, a significant difference between pre-test and post-test scores of the task-oriented coping dimension in Sport Competition Inventory was noted.